US-China policy on global trade: A survey of selected literature - Sousa, M.; Sousa, M.; Costa, R. L. da.; Rodrigues, C. (Global Trade and Customs Journal, 2020)
This study presents an analysis of research about US-China Policy on global trade, between 2015 and 2019. The research methodology was supported by a bibliometric analysis using Web of Science(WOS) and Scopus, broadening the understanding about the subject and understanding that there is a certain orientation of these studies for Policy. This article presents a demonstration of how research in US-China Policy on Global Trade has been treated by researchers in a global perspective. The research questions that guide this research were: RQ1: What were the main keywords present in studies of US-China Policy on Global Trade?; RQ2: Which sectors were studied on US-China Policy on Global Trade studies?; and RQ3: Which technologies were studied on US-China Policy on Global Trade studies? The main findings of this research are the trends identified on the studies analysed, namely, the most cited keyword that emerged from the literature review.